Material characterization of Nordic ski kick wax and its influence on performance - Michalek, A. J. (Sports Engineering, 2025)
Forward propulsion of classic-type cross country skis is traditionally accomplished by covering the middle portion of the ski base with a soft kick wax material. The purpose of this material is to maintain a low coefficient of dynamic friction at low contact pressures, while plastically deforming to conform to the snow surface (resulting in a high coefficient of static friction) at high contact pressure. This manuscript proposes a visco-plastic model of snow indentation into the wax surface as a mechanism for this behavior. Creep indentation was used to characterize the temperature-dependent mechanical properties of three representative wax products recommended for new, old, and transformed snow conditions. Numerical modeling was used to predict vertical force amplitudes required to produce a desired kicking force. The experimental results showed highly viscous behavior of all three products at sub-freezing temperatures, with viscosity decreasing with increasing from the product typically used on new snow to that used on transformed snow. Modeling results suggest that vertical preload of the ski prior to kicking may be essential to efficient skiing and confirms the relationship between snow granule size and preferable wax viscosity. These results suggest that creep indentation is an effective tool for characterizing ski wax properties and predicting their on-snow performance.